The Effectiveness of the Case Method Module in Improving the 21st Century Students' Ability to Manage Disasters - Wahyuni, Resma; Dipuja, Diah Anugrah (Journal of Educational Sciences, 2025)
Indonesia is a disaster-prone country that requires people to have disaster management skills. Disaster education is carried out through learning Environmental Science and Disaster Mitigation using case method-based modules. The purpose of the research is to evaluate the effectiveness of case-based modules in improving students' 21st century abilities including critical thinking, communication, collaboration, and creativity. This study used a pre-experimental design using a single-shot case study approach, which was conducted in two experimental classes without a control group. Data were collected using structured observation sheets based on standardized 4C skill indicators. The results of the study showed that the use of case-based modules improved students' 4C skills, including critical thinking, with an average score of 84.27 (class A) and 84 (class B) categorized as competent. Student communication class has an average score of 85.20 and class B 82.87 is categorized as competent. The collaboration of students is categorized as very competent with a grade A score of 85.67 and class B of 83.4. Students' creative abilities are categorized as competent in class A with an average of 85.13 and categorized as very competent in class B with an average of 83.27. Overall, the application of disaster management learning modules with case study methods is effective in improving students' 21st century competencies, especially in critical thinking, communication, collaboration, and creativity (4C).